2017
DOI: 10.3390/polym9060226
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Ene Photo-Click Collagen-PEG Hydrogels: Impact of Water-Soluble Photoinitiators on Cell Viability, Gelation Kinetics and Rheological Properties

Abstract: Thiol-ene photo-click hydrogels were prepared via step-growth polymerisation using thiol-functionalised type-I collagen and 8-arm poly(ethylene glycol) norbornene-terminated (PEG-NB), as a potential injectable regenerative device. Type-I collagen was thiol-functionalised by a ring opening reaction with 2-iminothiolane (2IT), whereby up to 80 Abs. % functionalisation and 90 RPN% triple helical preservation were recorded via 2,4,6-Trinitrobenzenesulfonic acid (TNBS) colorimetric assay and circular dichroism (CD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 60 publications
(126 reference statements)
5
58
2
Order By: Relevance
“…It can turn the solutions into gel much quicker than other photo initiators such as 1173, I‐2959, I‐250, and I‐260. In addition, it was found to be less harmful to cells compared with other photo initiators …”
Section: Introductionmentioning
confidence: 99%
“…It can turn the solutions into gel much quicker than other photo initiators such as 1173, I‐2959, I‐250, and I‐260. In addition, it was found to be less harmful to cells compared with other photo initiators …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the covalent gelatin-PCL co-network was carried out in the fibrous state via UV-initiated radical crosslinking reaction in the presence of (2-hydroxy-4-(2-hydroxyethoxy)-2methylpropiophenone) (I2959) as water-soluble, UV-compatible photoinitiator [68][69][70][71]. I2959 was selected since no toxic response was detected during cell culture with either bovine chondrocytes, human fetal osteoblasts or osteosarcoma cells with up to 0.5 mg·ml -1 I2959 [72][73][74]. To establish defined process-structure relationships, viscosity, surface tension, and electrical conductivity of the electrospinning solutions were measured and linked to fibre characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…SDS-PAGE was used to both elucidate the chemical composition of reacted products and to explore the triple helix organisation of methacrylated and HA-conjugated products. Retention of the triple helix architecture of collagen is key to enable resulting materials with chemotactic functionality, enhanced mechanical properties and decreased swellability [39]. Although we previously confirmed that collagen methacrylation had minimal effect on the collagen triple helix structure [40], the reaction of collagen-based polypetides with hydroxylamine has been reported to catalyse the chemical cleavage of peptide bonds between asparagine and glycine residues [58][59][60], which is likely to induce a denaturation of collagen triple helices.…”
Section: Analysis Of Collagen Conformationmentioning
confidence: 82%
“…polyacrylates [32] and respective hydroxamic acid-bearing derivatives [26], have been proposed as proof-of-concept anti-MMP substrates, due to the presence of ionically-charged and metal-chelating groups, respectively, along the polymeric backbone. [37][38][39]. UV-cured covalent networks made of functionalised collagen triple helices have also been presented with integrated MMP-chelating functions, whose swelling and compression properties can be controlled in a relatively independent fashion, via variation of e.g.…”
Section: Introductionmentioning
confidence: 99%